La inclusión educativa en los procesos pedagógicos. - Mena Rengel, Edith Dayana (2020)
The present research project aims to analyze educational inclusion in pedagogical processes, promoting cooperation among the educational community to improve the quality of the teaching-learning process and the effectiveness in the application of strategies that promote the development of social skills in children with special educational needs. Inclusive Education seeks to respond to the diversity of needs of all students, ensuring equal rights and opportunities. The methodological design of the research is framed in the synthetic analytical method, which was essential to determine the main problems of educational inclusion in the "Francesco Bernardone" Educational Unit. In order to obtain information for the development of our research, techniques and instruments were applied, among them a survey to teachers in which the following questions predominate The Educational Institution has carried out workshops on inclusive pedagogical strategies that promote the development of social skills of students with disabilities, do you promote the participation of students with disabilities in the classroom? in which we obtained a percentage of 75% and 87% respectively, in the Little answer option, for which we could determine that students with disabilities require the implementation of activities in the classroom aimed at peer socialization, verbal and non-verbal communication, emotional and behavioral self-regulation and most importantly that teaching is adapted to their rhythms and learning styles so that they can participate and progress in educational processes with curricular adjustments and structuring of interactive environments, establishing better alternatives for the construction of their knowledge, thus eliminating barriers to inclusion.